A cross-sectional study on the acceptability of self-collection for HPV testing among women in rural China. Issue 7 (29th May 2012) - Guan, YaoYao; Castle, Philip E; Wang, Shaoming; Li, Belinda; Feng, Changyan; Ci, Puwa; Li, Xue; Gravitt, Patti; Qiao, You-Lin
Abstract : Objective: To assess the acceptability of using self-collection as a method of sampling for human papilloma virus testing in rural China. Methods: 174 women from the national cervical cancer screening programme in Xiangyuan County, China, were enrolled in our study and underwent self-collection, clinician collection, colposcopy examination and were administered questionnaire. The questionnaire assessed the patients' preference and acceptability of collection method. Results: The mean overall acceptability score for self-collection, although significantly less than the overall score for clinician collection (p<0.01), still is well above 4 (4.33 of 5), indicating high acceptability. The acceptability scores for self-collection and clinician collection were not significantly different on scales measuring comfort and convenience (p>0.05). The scores were significantly lower for self-collection on scales measuring trust, ability to collect specimen and perceived effects of testing compared with clinician collection (p<0.01). 74% of participants preferred clinician collection, and of these participants, 86% preferred it because they thought the results were more accurate. Conclusions: The study shows that self-collection was highly acceptable and that self-collection and clinician collection were equally comfortable and convenient; however, the participants still preferred clinician collection because of lack of trust in the results of self-collection. This indicates that self-collection is an acceptable potential method for screening but education programmes about the validity of self-collection that target general population may be needed prior to implementation.